Career Adaptability of Marine Cadets: A Descriptive Study - Wiwik Sulistiani; Dewi Retno Suminar; Wiwin Hendriani (Universitas Ahmad Dahlan, 2019)
Issues pertaining to career often arise during higher education period. Common problems during such period of career development include choosing, deciding, and maintaining a career, including maintaining oneâ€™s choice of career. The aim of this study is to describe the career adaptability of shipping cadets. Participants are shipping cadets from a private university in Surabaya, Indonesia. Data was collected using an Indonesian version of Career Adaptability scale (CAAS). Result provides description on cadetsâ€™ career adaptability, as follows: 8% was categorized as â€œlowâ€, 23.2% â€œmoderateâ€, and 76% â€œhighâ€. Comparison of standard deviations shows that the career adaptability of shipping cadets had low variation. Percentages of each indicator are as follows: the indicator of â€œconcernâ€ ranked first (26.41%), â€œcontrolâ€ at second (25.85%), â€œconfidenceâ€ at third (24.24%), and â€œcuriosityâ€ at fourth (23.47%). It shows that all indicators of career adaptability among shipping cadets played roles in shaping career adaptability and have balanced similarities.